The Value and Consumer Properties of Pumpkin - Mukhtarovna, Nazirova Rahnamohon; Botiraliyevich, Usmonov Nodirjon; Inomjon ogli, Hojimatov Javlonbek (European Journal of Life Safety and Stability (2660-9630), 2022)
The article discusses the useful and dietary properties of pumpkin, the composition and chemical properties, as well as varieties of pumpkin. Its role as a product with pro and prebiotic properties is also considered. Pumpkin is rich in dietary fiber, so it serves as a breeding ground for anaerobic bacteria. They help in the digestion of food and inhibit the development of pathogenic intestinal microflora, absorb harmful substances and remove them from the body, acting as an enterosorbent.